Metodologia das escalas geográficas de poder e gestão aplicada à análise de desenvolvimento em quatro territórios rurais no Brasil - Aldomar A. Rückert; Anelise G. Rambo (Confins)
The present article results from a research project developed by a multi-disciplinary group, composed by researchers of different fields of knowledge as Geography, Agronomy, Economy and Sociology aimed to deal with a demand of the Territorial Development Office (SDT) of Agrarian Development Ministry (MDA) (Brazil) during the years of 2006-2007. Among other objectives, the research aimed to represent the different scales of action of actors in rural territories. It is presented here the action scales of actors in four projects developed in rural territories - the Regional Cooperative of Peasant Agriculture (CORAC), Seberi, (“Médio Alto Uruguai” territory /Rio Grande do Sul state); Small Farmers Milk Production Cooperatives Sistem (SISCLAF), Francisco Beltrão (“Sudoeste do Paraná Territory” / Paraná state); Small Peasant Agriculture Formation Center São José Operário (CENTAF), Silvânia, (“Estrada de Ferro” Territory / Goiás state) and Frutivale Association, Datas (“Vale do Jequitinhonha” Territory /Minas Gerais state). It is undertaken that the power and management geographic scales methodology, when applied to studies of territorial development, permits a clearer understanding of how territories are managed and who are the actors who interact in the development process. This allows to observe the potentialities and weakness of territory. These can be developed or be reduced respectively, in order to foment the territorial development processes. It may therefore serve as a tool for actions planning and territorial dynamics. The identification of the actors and scales has been made using interviews with half structured guide applied to leaders of development projects.